Real-world evidence: better than nothing or the future?: A perspective on clinical evidence generation in interventional oncology - Kaufmann, Nathalie; Pereira, Philippe L. (CardioVascular and interventional radiology, 2025)
Randomised controlled trials (RCTs) have traditionally been regarded as the gold standard in evidence-based medicine, providing a high level of evidence. However, mounting complexities, ranging from ethical issues and logistical barriers to rapid technological evolutions, have sparked interest in alternative or complementary evidence-generation methods. Real-world evidence (RWE) from large, well-designed research projects is increasingly viewed as powerful tools. Although RWE is sometimes perceived as “less robust” compared to RCTs due to potential biases, recent advances in study design, data capture, and analytical frameworks have highlighted its potential for shaping clinical practice and informing regulatory decisions. This article discusses the benefits and challenges of RWE within interventional oncology and explores whether it is merely “better than nothing” or indeed represents a key pillar of the future of clinical research.